RAPD diversity in Brazil nut (Bertholletia excelsa Humb. and Bonpl., Lecythidaceae) - Kanashiro, M; Harris, S; Simons, A (1997)
Estimates of randomly amplified polymorphic DNA (RAPD) variation within and between 5 provenances of Bertholletia excelsa (Brazil nut), a large South American rain forest tree, are presented. One hundred individuals of B. excelsa were screened for variation in 47 RAPD products, of which all but 6 (12.8%) of the products were polymorphic across the species. Estimates of the mean Shannon's phenotype diversity varied between 5.97 (Rio Branco) and 8.69 (Santarem) for each provenance and 10.580 for the species. An examination of the proportion of diversity present within and among provenances indicated that, on average, 68.7% of the variation occurred within provenances and only 31.3% of the observed variation resided between provenances.